The Effectiveness of Bubble Blowing Therapy to Reduce Pain in Children Undergoing Vaccination - Asih Fatriansari; Reva Afdila (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
Pain during vaccination is a significant factor that can increase anxiety and reduce children’s cooperation during immunization procedures. Simple non-pharmacological interventions, such as bubble blowing, are considered effective distraction techniques because they are inexpensive, easy to apply, and safe for children. This study aimed to determine the effectiveness of bubble blowing therapy in reducing pain among children undergoing vaccination. This research employed a quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of 20 children aged 3–5 years who received vaccinations at the Posyandu within the working area of Ambacang Padang Health Center. Pain levels were measured using the Face, Legs, Activity, Cry, and Consolability (FLACC) scale. Data were analyzed using univariate and bivariate analyses, with a paired t-test to assess differences before and after the intervention. The results showed that the average pain score before the bubble blowing intervention was 6.15 (SD = 1.27), categorized as moderate to severe pain. After the intervention, the average pain score decreased significantly to 2.45 (SD = 1.08), indicating mild pain. Paired t-test analysis revealed a significant difference between pre- and post-intervention pain scores (p = 0.000; p < 0.05). In conclusion, bubble blowing therapy is effective in reducing pain during childhood vaccination and is recommended as an evidence-based nursing intervention to enhance comfort, improve immunization experiences, and support parental adherence to vaccination schedules.